Deadly target [large type] - Goddard, Elizabeth (Goddard, Elizabeth. Rocky Mountain courage, 2022)
"Criminal psychologist Erin Larson's dreams of a successful career come to a screeching halt when she nearly loses her life in a boating accident and then learns that her mother tried to commit suicide. She leaves her job to care for her mother in Montana. At least there Erin is able to produce her podcast, which focuses on solving missing persons cold cases. Nathan Campbell's father was investigating such a case when he was shot, and now Nathan needs to enlist Erin's help to solve the case. She's certainly good at what she does. The only problem? She's his ex. As the two dig deeper, it becomes clear that they, too, are being targeted--and the answers to their questions are buried deep within the past Erin struggles to explain and longs to forget."--